Revival of ferromagnetic-metallic phase and emergence of Griffiths phase via Ni and Cr substitution in charged-ordered Pr0.75Na0.25MnO3 manganite / Rozilah Rajmi … [et al.] - Rajmi, Rozilah; Ibrahim, Norazila; Mohamed, Zakiah; Sheikh Abdul Aziz, Siti Sumaiyah (Research Management Institute (RMI), 2023)
Polycrystalline samples of Pr0.75Na0.25Mn1-xAxO3(A = Ni, Cr; x = 0, 0.03) were prepared using conventional solid-state method and their structural and magnetic properties were investigated. Monovalent-doped Pr0.75Na0.25MnO3 exhibits insulating behavior which is related to the strong localization of charge carriers due to the presence of charge ordering (CO). The substitution of different of magnetic ions, A, which are Ni2+ and Cr3+, at a concentration of x = 0.03 at the Mn site in the CO Pr0.75Na0.25Mn1-xAxO3 manganite, has been found to dramatically modify its structural and magnetic properties. X-ray diffraction patterns showed that all samples were present in single phase and crystallized in orthorhombic structure with Pnma space group. The Rietveld refinement analysis showed that the unit cell volume increased due to Ni2+ substitution, while it decreased due to Cr3+ substitution, which may be attributed to the different ionic radii of both ions. The suppression of the CO state and the induction of the ferromagnetic-metallic state in the Ni-substituted and Cr-substituted samples are suggested to be due to the induction of double-exchange interaction involving Ni2+–O–Mn4+ and Mn3+–O–Cr3+, respectively.